Synthesis of arctigenin derivatives against infectious hematopoietic necrosis virus - Hu, Yang; Liu, Lei; Li, Boyang; Shen, Yufeng; Wang, Gao-Xue; Zhu, Bin (European journal of medicinal chemistry, 2019)
Infectious hematopoietic necrosis virus (IHNV) is a common pathogen that causes severe disease and huge economic losses in the salmonid aquaculture industry. Herein, a series of arctigenin derivatives are synthesized to evaluate their antiviral activity against IHNV. The results indicate that the length of linker and imidazole substituent groups play an important role in decreasing IHNV replication. In this study, the arctigenin–imidazole hybrid derivative 15 with an eight carbon atoms length of the linker reduces IHNV replication with an IC50 value of 1.3 μM. In addition, derivative 15 significantly inhibits apoptosis and cellular morphological damage induced by IHNV. Mechanistically, derivative 15 can not damage the viral particle directly. While time-of-addition and viral binding assays reveal that derivative 15 mainly affect the early replication of IHNV but do not interfere with IHNV adsorption. Overall, derivative 15 could be considered to develop as a promising agent to treat IHNV infection. [Display omitted] •Arctigenin-imidazoles with anti-IHNV properties were synthesized.•Eight carbon atoms length of the linker (R1 substituted position) and imidazole (R2 substituted position) could significantly increase the anti-IHNV activity of arctigenin derivatives.•Derivative 15 might inhibit the early events of IHNV replication.